Magnus Chase and the sword of summer - Riordan, Rick (UK, Puffin books- Penguin Random House, 2016)
My name is Magnus Chase. I'm orphaned and living rough on the streets of Boston. And things are about to get much worse. My day started out normally enough. I was sleeping under a bridge when some guy kicked me awake and said, 'They're after you.' Next thing I know, I'm reunited with my obnoxious uncle, who casually informs me that my long-lost father is a Norse god. Nothing normal about that. And it turns out the gods of Asgard are preparing for war. Apparently, if I can't find the sword my father lost two thousand years ago, there will be doom. Doomsday, to be precise. A fire giant attacking the city? Immortal warriors hacking each other to pieces? Unkillable wolves with glowing eyes? It's all coming up. But first I'm going to die. This is the story of how my life goes downhill from there
Keywords: English fiction